Non-defendant bad character and s. 100 of the Criminal Justice Act 2003: A socio-legal analysis of admissibility gateways and trial tactics. (January 2023) - Thomason, Matt
This article presents a socio-legal analysis of the use of non-defendant bad character evidence in Crown Court criminal trials in England. Combining an in-depth doctrinal analysis of s. 100 of the Criminal Justice Act 2003 with original qualitative empirical methods (interviews with trial counsel and observations of real Crown Court trials), the article explores the real-life practical operation of this rule of exclusion and its associated inclusionary exceptions, and the role that non-defendant bad character can have on trial tactics of counsel. In doing so, it argues that illogical Court of Appeal decisions on the use of bad character for credibility purposes are causing confusion in practice, that the 'tit-for-tat' gateway for defendant bad character is a more significant hurdle than s. 100 itself, and that counsel often eschew bad character applications for fear of alienating the jury.